2014
DOI: 10.1111/bph.12627
|View full text |Cite
|
Sign up to set email alerts
|

Different mechanisms of homologous and heterologous μ‐opioid receptor phosphorylation

Abstract: The efficiency of μ‐opioid receptor signalling is tightly regulated and ultimately limited by the coordinated phosphorylation of intracellular serine and threonine residues. Here, we review and discuss recent progress in the generation and application of phosphosite‐specific μ‐opioid receptor antibodies, which have proved to be excellent tools for monitoring the spatial and temporal dynamics of receptor phosphorylation and dephosphorylation. Agonist‐induced phosphorylation of μ‐opioid receptors occurs at a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 47 publications
(97 reference statements)
5
48
0
Order By: Relevance
“…The present results suggest that PKC-mediated phosphorylation of S363 and T370 (Doll et al, 2011;Feng et al, 2011;Illing et al, 2014;Mann et al, 2015) is not necessary because morphine-induced desensitization persisted when all S/T sites were mutated. Chu et al (2010) reported that morphine-induced, PKC-mediated desensitization is mediated partly by phosphorylation of Ga i2 subunits, which should be independent of C-terminal phosphorylation.…”
Section: Tsstmentioning
confidence: 65%
See 2 more Smart Citations
“…The present results suggest that PKC-mediated phosphorylation of S363 and T370 (Doll et al, 2011;Feng et al, 2011;Illing et al, 2014;Mann et al, 2015) is not necessary because morphine-induced desensitization persisted when all S/T sites were mutated. Chu et al (2010) reported that morphine-induced, PKC-mediated desensitization is mediated partly by phosphorylation of Ga i2 subunits, which should be independent of C-terminal phosphorylation.…”
Section: Tsstmentioning
confidence: 65%
“…Desensitization by ME and morphine were both unaffected in 3S/T-A that removes S375, which is efficiently phosphorylated by GRK2/3, as well as two proximal residues, T370, that is quite efficiently phosphorylated (Doll et al, 2011), and S363 which is constitutively phosphorylated and a substrate for PKC-phosphorylation (Illing et al, 2014;Mann et al, 2015). This finding suggests other S/T residues may be phosphorylated to contribute to desensitization and internalization.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The CA state of MOR is thought to depend on receptor modifications, including receptor interactions with accessory proteins or phosphorylation at numerous sites on MOR (Sadee et al, 2005, Connor and Traynor, 2010, Mann et al, 2014), including constitutive phosphorylation at S363 in vivo (Illing et al, 2014). With the emergence of phosphosite-specific MOR antibodies and other pharmacological tools (Mann et al, 2014), future studies could determine whether CFA increases MOR phosphorylation or dephosphorylation that then contributes to MOR CA .…”
Section: Mu Opioid Receptor Constitutive Activity (Morca) Inhibits Lsmentioning
confidence: 99%
“…With the emergence of phosphosite-specific MOR antibodies and other pharmacological tools (Mann et al, 2014), future studies could determine whether CFA increases MOR phosphorylation or dephosphorylation that then contributes to MOR CA .…”
Section: Mu Opioid Receptor Constitutive Activity (Morca) Inhibits Lsmentioning
confidence: 99%